Incidence of new outpatient long-acting reversible contraceptive insertions among a commercially insured, US population from 2010 to 2020 - Clara E. Busse; Chase D. Latour; Sara Z. Dejene; Andrea K. Knittel; Mollie E. Wood; Alan C. Kinlaw; Mekhala V. Dissanayake (Contraception: X, 2023)
Objectives: Characterize new use of long-acting reversible contraceptives (LARCs), highly effective contraceptive methods, in a broad population over time. Study Design: We constructed a retrospective cohort of commercially insured individuals aged 15 to 54 years from 2010 to 2020 and estimated monthly incidence of new LARC insertions. Results: The monthly standardized incidence increased from 6.0 insertions per 10,000 individuals in January 2010 to 14.1 in December 2020, with a dip in insertions after March 2020. Hormonal intrauterine devices were consistently the most inserted LARC; implants were increasingly favored over time. Conclusions: LARCs are increasingly popular forms of contraception among commercially insured individuals. Implications: Given the increasing popularity, ensuring access to LARCs is critical.